2010
DOI: 10.1007/s00439-010-0815-6
|View full text |Cite
|
Sign up to set email alerts
|

A single nucleotide polymorphism in the FADS1/FADS2 gene is associated with plasma lipid profiles in two genetically similar Asian ethnic groups with distinctive differences in lifestyle

Abstract: Recent genome-wide association studies (GWASs) showed that single nucleotide polymorphisms (SNPs) in FADS1/FADS2 were associated with plasma lipid concentrations in populations with European ancestry. We investigated the associations between the SNPs in FADS1/FADS2 and plasma concentrations of triglycerides, high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) in two Asian groups, i.e., Japanese and Mongolians. The genotype of rs174547 (T/C), found to be associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 18 publications
(26 reference statements)
6
56
0
Order By: Relevance
“…Recent GWA studies have also identifi ed several genetic loci in the FADS gene cluster that are associated with blood lipid levels (18)(19)(20)(21). However, we were unable to replicate previously reported associations with plasma lipids, particularly LDL-cholesterol ( 13,22,30 ). This most likely relates to the fact that lipids are distal phenotypes that are infl uenced by many genes and environmental factors in addition to desaturase activity, and our study sample lacked the power to detect signifi cant FADS genotype associations at baseline.…”
Section: Snp Associations With Plasma and Erythrocyte Variables Aftermentioning
confidence: 64%
See 1 more Smart Citation
“…Recent GWA studies have also identifi ed several genetic loci in the FADS gene cluster that are associated with blood lipid levels (18)(19)(20)(21). However, we were unable to replicate previously reported associations with plasma lipids, particularly LDL-cholesterol ( 13,22,30 ). This most likely relates to the fact that lipids are distal phenotypes that are infl uenced by many genes and environmental factors in addition to desaturase activity, and our study sample lacked the power to detect signifi cant FADS genotype associations at baseline.…”
Section: Snp Associations With Plasma and Erythrocyte Variables Aftermentioning
confidence: 64%
“…Blood samples for analysis were drawn after a minimum 8 h overnight fast cholesterol (HDL-C) ( 20,21 ), and higher triglyceride concentrations ( 21 ), suggesting that altered desaturase activities may impact plasma lipoprotein levels. Previous studies have suggested that dietary intake of different PUFAs interact with FADS1 variation to affect blood lipids ( 13,22 ).…”
Section: Blood Sampling and Analysismentioning
confidence: 99%
“…It is possible that the limited sample size and different dyslipidemia pattern may explain the null fi ndings for total and LDL cholesterol in the current study. Furthermore, distinctive diet and lifestyle may also modify the effects of FADS1 on lipid metabolism, even in genetically similar populations ( 12 ), which might serve as another plausible explanation for these studies might be explained by higher conversion rate of 22:5n-3 to DHA in pregnant women but not in general populations ( 10 ). The associations between FADS1 rs174550 and lipids in the current study were in line with results from a meta-analysis of 122,743 nondiabetic participants ( 15 ), although signifi cant associations were also detected between the genetic variant Data are means ± SE or n. P values were adjusted for age, sex, BMI, residence (urban/rural), and region (Beijing/Shanghai) using an additive model.…”
Section: Discussionmentioning
confidence: 99%
“…The association of the FADS1 gene variants with serum lipid compositions has been reported by a number of GWAS [14,39,40]. We studied the FADS (rs174547) polymorphism because it was investigated in pediatric populations.…”
Section: Discussionmentioning
confidence: 99%
“…The fatty acid desaturase 1 (FADS1) gene encodes fatty acid desaturase enzymes which regulates the desaturation of fatty acids [14].…”
Section: Introductionmentioning
confidence: 99%